SCHOOL OF PARENTING KELUARGA SAMARA (MEWUJUDKAN KELUARGA SAKINAH MAWADDAH WAROHMAH): Indonesia - Rachmawaty, Farida Juliantina; Jeem, Yaltafit Abror (UII, 2025)
Marriage is not merely the completion of half of one's religion, a Sunnah of the Prophet that his followers should carry out, but also to produce a superior generation, both in character and deeds. Individuals who are about to marry should have a foundation of knowledge to build a harmonious family, Sakinah mawaddah warohmah (a harmonious family). However, in reality, most individuals are preoccupied with pursuing careers to meet the demands of life, but on the other hand, they do very little to prepare themselves to build a family. As a result, families are formed based solely on acquired experiences without knowing what is right or wrong or what is ideal. Consequently, many family problems arise, such as divorce, family disputes, juvenile delinquency, drug use, and others, which often break our hearts. Motivated by these issues, the School of Parenting Keluarga Samara (Creating a Harmonious Family, Shaping a Superior Generation) online program aims to provide a foundation for young families or future parents to build a strong and harmonious family and to produce a superior generation. The training is conducted with participants joining a WhatsApp group. Subsequently, participants receive structured material online through Zoom meetings. Pre-tests and post-tests are conducted before and after each material delivery. Alhamdulillah, the results of this activity have had a positive impact on the community, as the pre-test and post-test results show a significant difference between before and after participating in the activity, with a significance level of 0.000 (p<0.05). The post-test results show better results compared to the pre-test.